Efficacy and Safety of EUS-directed Transgastric ERCP (EDGE) vs Laparoscopic-Assisted ERCP: : A Systematic Review and Meta-Analysis - Gangwani, Manesh (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.